From information literacy assessment to information behaviour: A case study of Malaysian secondary school students / Hani Syazillah Nordin - Hani Syazillah , Nordin (2019)
This study uses a multiple method case study to investigate the complementarity between information literacy (IL) and information behaviour (IB), specifically to understand how students’ information behaviour may have formed their information literacy skills. Few studies have explored the relationship between these two major sub-disciplines of library and information science. With a focus on Malaysian secondary school students, this case study is designed in two distinct phases. In Phase I, the aim was to develop a valid adapted measurement toll for information literacy skills assessment of Malaysian secondary school students. A total of 146 secondary school students aged 16 were evaluated on their information literacy skills using an adapted and validated Tool for Real-time Assessment of Information Literacy Skills (TRAILS-9). This phase contributes to the adaptation, translation and validation of an IL assessment tool and also to ascertain the IL skills level of the respondents in this study. Phase II was designed to understand the information behaviour of high achieving secondary school students; based on their academic achievement and IL skills level. This phase involved 17 informants for the first cycle involving investigation of IB based on academic tasks, while the second cycle involved 6 informants in investigating their IB during a leisure activity. The first cycle in this phase data was collected through interviews, document analysis and task assessment using flowcharts. Findings reveal that TRAILS can be adapted for assessing Malaysian students’ IL skills level. Overall the students’ IL performance level was at an average. Based on their IL score and academic achievement level, the students were categorized to four cohorts - revealing that not all high achieving students have high level of IL skills. Some of the low academic achieving students were somewhat more competent in IL skills, specifically in using information responsibly and ethically. However, low acheiving students were less competent in ‘evaluating sources and information’. The examination of students’ project work (to elicit evidences of IL skills) and interviews with students revealed that there are slightly differences in the information behaviour between the informants according to the groups. Using Winston’s IB model and Hektor’s Information Activity model, the information behaviour and information literacy of the students is depicted in a proposed complementarity IL-IB framework. This study has contributed to developing a valid and reliable systematic mechanism to adapt a pre-existing instrument to assess IL skills of secondary schools students. The study also provides empirical evidence to map the relationship or complementarity of information literacy (IL) and information behaviour (IB). School authorities need to understand students’ information behaviour to inculcate the development of information literacy skills in advancing their academic acheivements.